2022
DOI: 10.3390/ijerph191811483
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 in Children with Chronic Lung Diseases

Abstract: Background: since December 2019, the world has become victim of the coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). The aim of our narrative review is to analyze the impact of COVID-19 in children suffering from chronic lung disease (CLD). Methods: we searched the MEDLINE/Pubmed database using the terms “SARS-CoV-2” or “COVID-19” or “Coronavirus Diseases 2019”; AND “chronic lung diseases” or “chronic respiratory diseases” or “asthma” or “cyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…In the current study, the spirometry values at the third and sixth months after COVID-19 infection were similar to those measured before the infection and could be due to the patients having had a mild infection. Although COVID-19 infection has a mild course in children, 20 21 patients with ongoing respiratory symptoms after the infection should be followed up with respiratory function tests.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the spirometry values at the third and sixth months after COVID-19 infection were similar to those measured before the infection and could be due to the patients having had a mild infection. Although COVID-19 infection has a mild course in children, 20 21 patients with ongoing respiratory symptoms after the infection should be followed up with respiratory function tests.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Ferraro et al published a 2022 scoping review that mainly looked at the effect of healthcare delivery on children's disease status. 15 Hence, we aimed to conduct a systematic review and meta-analyses to determine the prevalence of SARS-CoV-2 infection, factors affected by severe COVID-19, and associated complications of COVID-19 in children with CLD.…”
Section: Coronavirus Disease 2019 (Covid-19mentioning
confidence: 99%
“…They found that 3.4% of the pediatric population had COVID-19 infection, with only one child requiring hospitalization. 15…”
Section: Completeness Of Evidencementioning
confidence: 99%
See 2 more Smart Citations